Final answer:
To rewrite the function f(x) = 4x²+12x+9 by completing the square, follow the steps: factor out the coefficient of x², complete the square inside the parentheses, simplify and factor the inside quadratic expression, and rewrite the function in its completed square form.
Step-by-step explanation:
To rewrite the function f(x) = 4x²+12x+9 by completing the square, we follow these steps:
- Factor out the coefficient of x², which in this case is 4: f(x) = 4(x²+3x)+9
- Complete the square inside the parentheses by adding half of the coefficient of x (3/2 in this case) squared: f(x) = 4(x²+3x+9/4)+9-9/4
- Simplify and factor the inside quadratic expression as a perfect square: f(x) = 4(x+3/2)²+9-9/4
- Simplify further and rewrite the function in its completed square form: f(x) = 4(x+3/2)²+27/4